DIMENSI KONFLIK, INDEPENDENSI, DIALOG DAN INTEGRASI ANTARA ISLAM DAN SAINS - Firzan Nadia Fatiq, Diska; Sudirman (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2024)
This paper aims to examine the relationship between Islam and science from the perspectives of conflict, independence, dialogue, and integration. This study employs a literature review approach, drawing on various references and sources as the foundation. The findings indicate that the four models of the relationship between Islam and science conflict, independence, dialogue, and integration represent a spectrum of perspectives in understanding the interaction between these two disciplines. In the Islamic tradition, the approaches of independence and dialogue tend to be more dominant, with an increasing number of Muslim scholars and scientists advocating for the integration of scientific discoveries with religious teachings. This approach underscores the importance of collaboration between science and religion in achieving a deeper understanding of the universe and the purpose of human life. Keywords: Conflict, Independence, Dialogue, Integration of Islam and Science